2015
DOI: 10.1186/s12966-015-0267-4
|View full text |Cite|
|
Sign up to set email alerts
|

Is self-weighing an effective tool for weight loss: a systematic literature review and meta-analysis

Abstract: BackgroundThere is a need to identify effective behavioural strategies for weight loss. Self-weighing may be one such strategy.PurposeTo examine the effectiveness of self-weighing for weight loss.MethodsA systematic review and meta-analysis of randomised controlled trials that included self-weighing as an isolated intervention or as a component within an intervention. We used sub groups to analyse differences in frequency of weighing instruction (daily and weekly) and also whether including accountability affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 50 publications
2
86
1
1
Order By: Relevance
“…Recruiting participants with friends increases the availability of social support, and results in higher rates of weight loss treatment completion as well as better weight loss maintenance . Finally, the regular monitoring and individual feedback on weight and diabetes outcomes from the study staff were substantial facilitators of adherence to the VLED in the present study and a well‐documented phenomenon in a number of systematic reviews . Individuals who self‐weigh regularly lose more weight and also consume fewer calories than people who do not monitor their weigh regularly .…”
Section: Discussionmentioning
confidence: 65%
“…Recruiting participants with friends increases the availability of social support, and results in higher rates of weight loss treatment completion as well as better weight loss maintenance . Finally, the regular monitoring and individual feedback on weight and diabetes outcomes from the study staff were substantial facilitators of adherence to the VLED in the present study and a well‐documented phenomenon in a number of systematic reviews . Individuals who self‐weigh regularly lose more weight and also consume fewer calories than people who do not monitor their weigh regularly .…”
Section: Discussionmentioning
confidence: 65%
“…As shown in Table , we identified 34 unique meta‐analyses of RCTs investigating nonpharmacological interventions for weight loss in obese adults, which were derived from 26 unique references …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, among 20 meta‐analyses comparing two “active” interventions, 12 experimental interventions were found to be superior to comparison groups across examined outcomes per random‐effects calculations. These outcomes included an overall reduction in weight (motivational interviewing in addition to active intervention vs mixed interventions without motivational interviewing, self‐weighing in addition to diet and exercise vs mixed interventions without self‐weighing, low‐carbohydrate non‐energy‐restricted diets vs low‐fat energy‐restricted diets, hypocaloric low‐carbohydrate diets vs low‐fat diets, diet and exercise vs diet alone, low‐carbohydrate vs normal or high‐carbohydrate diets and vegetarian vs nonvegetarian diet); a decrease in BMI (motivational interviewing in addition to active interventions vs mixed interventions without motivational interviewing and nutritional interventions in metabolically healthy obese subjects vs other types of interventions); a decrease in body fat (low‐carbohydrate diets vs low‐fat diets and low‐carbohydrate vs normal or high‐carbohydrate diets); and a decrease in waist circumference (Internet‐delivered lifestyle interventions vs minimal interventions). Of these 12, 10 also were statistically significant at P < 0.005.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, self‐weighing resulted in inconsistent results, where in some studies daily self‐weighing and visual feedback facilitated minimal weight loss and its maintenance, while in other studies weighing every day led to greater adoption of weight control behaviours and generated greater weight loss . In fact, it was suggested that there is insufficient evidence as to whether self‐weighing without other intervention components is effective . Two systematic reviews specifically examined self‐weighing for weight management, and both concluded that regular self‐weighing appeared to be a good predictor of moderate weight loss, less weight regain or avoidance of initial weight gain in adults …”
Section: Discussionmentioning
confidence: 99%